Анализа корелације серума CRK, CD138 и APL са прогнозом код пацијената са дијабетичком нефропатијом: Серум CRK, CD138 и APL код дијабетичке нефропатије - Chen, Yibo; Li, Li; Xia, Rui (Journal of Medical Biochemistry, 2026)
Objective To explore the relationships between the levels of serum CITRON kinase-related kinase (CRK), syndecan-1 (CD138), and APJ receptor ligand (APL) and renal function and prognosis in patients with diabetic nephropathy.Methods From November 2023 to November 2025, 306 patients with diabetic nephropathy admitted to the hospital were selected as the study group, while 306 patients with simple diabetes were selected as the simple diabetes group; another 306 healthy individuals who underwent physical examinations during the same period composed the healthy control group. The levels of serum CRK, CD138, and APL were determined via enzyme-linked immunosorbent assay. Pearson correlation analysis was used to investigate the correlation between the levels of serum CRK, CD138, and APL and the clinical data of patients with diabetic nephropathy. To examine the variables determining a poor prognosis in patients with diabetic nephropathy, univariate and multivariate logistic regression analyses were performed. The prognostic usefulness of serum CRK, CD138, and APL levels for the unfavorable prognosis of individuals with diabetic nephropathy was examined using receiver operating characteristic (ROC) curves.Results Compared with those in the healthy control group, the levels of serum CRK and CD138 in patients in the simple diabetes group and the study group were increased, whereas the level of APL was decreased. The estimated glomerular filtration rate (eGFR) of patients in the study group decreased, and the ratio of urinary albumin to creatinine (UACR) increased. All these differences were statistically significant (P < 0.05). The levels of serum CRK, CD138, and APL and the UACR in the study group were greater than those in the simple diabetes group, whereas the eGFR was lower than that in the simple diabetes group. All these differences were statistically significant (P < 0.05). Pearson correlation analysis revealed that the levels of serum CRK, CD138, APL, and UACR in the study group were negatively correlated with the eGFR (P < 0.05) and positively correlated with the renal disease stage, creatinine, 24-hour proteinuria, and UACR indicators (P < 0.05). Serum CRK, CD138, and APL levels, as well as the UACR, were higher (P < 0.05) and the eGFR was lower (P < 0.05) in the bad prognosis group than in the good prognosis group. Univariate and multivariate logistic regression analysis showed that serum CRK, CD138, and APL levels all had an impact on patients' prognoses (P < 0.05). The results of the ROC curve analysis revealed that the combined area under the curve (AUC) of serum CRK, CD138, and APL for predicting poor prognosis was significantly greater than that of CRK (Z = 2.857, P = 0.007), CD138 (Z = 2.429, P = 0.018), and APL (Z = 2.175, P = 0.033).Conclusion The levels of CRK, CD138 and APL in the serum of patients with DN increase, and these increases are related to renal function. The combination of these three indicators has greater predictive efficacy for the prognosis of patients.
Keywords: Дијабетичка нефропатија; ЦИТРОН киназа-повезана киназа; Мултилигандни протеогликан-1; Лиганд рецептора APJ; Бубрежна функција; Прогностичка анализа